Directors’ Remuneration and Corporate Social Responsibility : A Study on Malaysian Listed Firms - Mohd Waliuddin, Mohd Razali; Hew, Jing Ying; Janifer, Lunyai; Noraisyah, Abd Rahman (Sciedu Press, 2019)
The main objective of this paper is to examine the relationship between directors’ remuneration and Corporate Social Responsibility (CSR) for listed firms in Malaysia. All financial data such as firm size, performance and leverage can be collected from Thomson Reuters DataStream while directors’ remuneration and CSR disclosures were collected from annual reports. 377 samples of listed firms on Bursa Malaysia were collected from year 2014 to 2016. The results of this study show that increase director’ remuneration motivates the directors to perform higher CSR. The CSR practices should benefit people and firms. Therefore, more benefits gained by public and firms from CSR should not be compensated with low directors’ remuneration. The results also show that firm size and leverage have positive relationship with CSR. This study can be extended using other measurements of CSR such as Global Reporting Initiative (GRI), human rights and environmental reporting which could give new insights on the relationship between CSR and directors’ remuneration.